The chromatin remodeling and mRNA splicing functions of the Brahma (SWI/SNF) complex are mediated by the SNR1/SNF5 regulatory subunit. - Zraly, C.B.; Dingwall, A.K. (Nucleic Acids Research, 2012)
Nucleosome remodeling catalyzed by the ATP-dependent SWI/SNF complex is essential for regulated gene expression. Transcriptome profiling studies in flies and mammals identified cell cycle and hormone responsive genes as important targets of remodeling complex activities. Loss of chromatin remodeling function has been linked to developmental abnormalities and aggressive cancers. The Drosophila Brahma (Brm) SWI/SNF complex assists in reprogramming and coordinating gene expression in response to ecdysone hormone signaling at critical points during development. We used RNAi knockdown in cultured cells and transgenic flies, and conditional mutant alleles to identify unique and important functions of two conserved Brm complex core subunits, SNR1/SNF5 and BRM/SNF2-SWI2, on target gene regulation. Unexpectedly, we found that incorporation of a loss of function SNR1 subunit led to alterations in RNA polymerase elongation, pre-mRNA splicing regulation and chromatin accessibility of ecdysone hormone regulated genes, revealing that SNR1 functions to restrict BRM-dependent nucleosome remodeling activities downstream of the promoter region. Our results reveal critically important roles of the SNR1/SNF5 subunit and the Brm chromatin remodeling complex in transcription regulation during elongation by RNA Polymerase II and completion of pre-mRNA transcripts that are dependent on hormone signaling in late development.